PENGARUH KECERDASAN INTRAPERSONAL DAN KONSEP DIRI TERHADAP PRESTASI BELAJAR MATEMATIKA - Christin Monica; Leonard Leonard (Jurnal Lingkar Mutu Pendidikan, 2024)
The purpose of this research is to find out: (1) the influence of intrapersonal intelligence and self-concept on mathematics learning achievement; (2) the influence of intrapersonal intelligence on mathematics learning achievement; (3) the influence of self-concept on mathematics learning achievement. The method used in this research is a survey method using descriptive analysis. The sample was obtained using the Non Probability Sampling technique as many as 62 students from class X SMK PGRI 2 Depok. Data analysis consisted of descriptive analysis, data analysis requirements test, and hypothesis testing. The data analysis requirements test used were normality test, linearity test and multicollinearity test. The results of hypothesis testing with a significant level of 5% or α = 0.05, namely (1) there is a significant influence between intrapersonal intelligence and self-concept on mathematics learning achievement. (2) there is a significant influence between intrapersonal intelligence on mathematics learning achievement. (3) there is a significant influence between self-concept on mathematics learning achievement.